Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Genome-wide investigation of methyl-CpG-binding domain genes in Brassica napus L. and functional characterization of BnaC09.MBD7 and BnaA10.MBD7 in modulating osmotic stress tolerance - Ling Jiang; Gang Lin; Mufei Shi; Jingying Wu; Lixuan Sun; Xiumei Xu; Zhihua Zhang; Shiyao Wen; Meifeng Chen; Xiewang Gao; Mu Xiao (Physiology and Molecular Biology of Plants, 2026)

Engineering an amino-modified MOF@COF interface to construct a light-responsive oxidase-like nanozyme for rapid total antioxidant capacity assay in foods - Yanhui Feng; An Xu; Huan Li; Xiumei Lin; Hongxu Guo (Food Chemistry, 2026)

WNT4 reprograms dental pulp stem cells to resist PANoptosis and rebuild neurogenic potential for facial nerve injury repair - Wanqiu Xu; Hualei Xi; Song Lin; Lihong Yao; Jian Sun; Bing Xue; Guiyan Piao; Ying Liu; Wenjing Sun; Xiumei Wang (Inflammation Research, 2026)

The effective adsorption of cobalt from radioactive wastewater by sulfonated g-C3N4 - Yusen Liu; Sinan Chen; Yifan Li; Xiangyi Du; Zhiyi Wang; Xiumei Wang; Hanbao Chong; Mingzhang Lin (Annals of Nuclear Energy, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

Unlocking synergistic adsorption through Cr3+ coordination in azamacrocycles - Sinan Chen; Hang Zhang; Xiumei Wang; Yusen Liu; Yifan Li; Xiangyi Du; Linfeng Nong; Zhiyi Wang; Mingzhang Lin (Chemical Engineering Journal, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Exploring the future of sustainable ocean economies: Marine Trade's role in advancing inclusive green growth - Chunyu Lin; Guilin Dai; Ying Liu; Guanqiong Ye; Xiumei Fu (Ocean & Coastal Management, 2026)

A novel ternary system for enhanced uranium extraction from low-acidity solutions: Performance and mechanism - Xiumei Wang; Qiqi Guo; Zhihao Wu; Yusen Liu; Sinan Chen; Yifan Li; Mingzhang Lin (Journal of Environmental Chemical Engineering, 2025)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

How to promote green transformation of mariculture industry under the influence of financial constraints? A policy simulation based on peer incentive perspective - An Yan; Ying Liu; Chunyu Lin; Wenwen Gu; Qiaorong Yin; Xiumei Fu (Marine Pollution Bulletin, 2025)

Carbon-coated Cd0.9Zn0.1S for photocatalytic oxidation of benzyl alcohol to hydrobenzoin and H2 - Lichao Lin; Xiumei Li; Zizhong Zhang; Yongfan Zhang; Jinni Shen; Tao Ji; Wenyue Su (Chemical Engineering Journal, 2025)

ROS acted as an initial role in selenium nanoparticles alleviating insecticide chlorpyrifos-induced oxidative stress, pyroptosis, and intestinal barrier dysfunction in porcine intestinal epithelial cells - Minna Qiu; Zhiyu Hao; Yuhao Liu; Yuhang Liu; Minghang Chang; Xu Lin; Xiumei Liu; Na Dong; Wei Sun; Xiaohua Teng (Pesticide Biochemistry and Physiology, 2025)

Quantifying the impacts of climate change and human activities on vegetation in ecologically fragile regions: a case study of Northern China - Xiangzhou Dou; Xiumei Li; Guoqing Sang; Ping Yang; Yuhu Zhang; Jianing Wang; Zhicheng Zhong; Feng Lin; Qiang Zhao (Theoretical and Applied Climatology, 2025)

Decreases in frequency-dependent intrinsic activity of the default mode network are associated with depression and cognition in patients with postacute sequelae of SARS-CoV-2 infection - Yao Wang; Ziwei Yang; Xiumei Zheng; Xiao Liang; Lin Wu; Chengsi Wu; Jiankun Dai; Yuan Cao; Xianjun Zeng; Meng Li; Fuqing Zhou (Brain Structure and Function, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Sinensetin Inhibits Angiogenesis in Lung Adenocarcinoma via the miR-374c-5p/VEGF-A/VEGFR-2/AKT Axis - Tao Ji; Lin Ye; Erping Xi; Ying Liu; Xiumei Wang; Sha Wang (Cell Biochemistry and Biophysics, 2024)

Molecular mechanism of apoptosis induced by 4-tBP in common carp (Cyprinus carpio L.) head kidneys was explored from various angles: Hippo pathway, miR-203a, oxidative stress, ER stress, and mitochondrial pathway - Jiatian Liang; Xu Lin; Chunyu Jiang; Yuhao Liu; Zhiyu Hao; Minna Qiu; Xiumei Liu; Dechun Chen; Xiaohua Teng; You Tang (Aquaculture, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Occurrence of Cladosporium herbarum causing leaf spot on Avena sativa in China - Jiangui Zhang; Guiqin Zhao; Jikuan Chai; Liang Zeng; Wenlong Gong; Fu Ran; Xiumei Nie; Ruifang Zhang; Doudou Lin (Crop Protection, 2024)

Formulation with zinc acetate enhances curcumin's inherent and photodynamic antimicrobial effects for food preservation - Liyun Chen; Xiumei Li; Jingyi Chen; Ranxun Lin; Yuhan Mai; Yuxin Lin; Guodong Wang; Zheng Chen; Wei Zhang; Jiang Wang; Cai Yuan; Longguang Jiang; et al. (Food Control, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

A Borehole Acoustic Calculation Approach with Gas Hydrate Saturation Inversion in Gas Hydrate-Bearing Sediments - Lin Liu; Xiumei Zhang; Xiuming Wang (Journal of Marine Science and Engineering, 2024)
The inversion of gas hydrate saturation is a critical procedure in the evaluation of hydrate reservoirs. In this paper, a theoretical model for a borehole acoustic wavefield excited by multipole sources is established for the first time. On this basis, the attenuation of the dipole flexural waves is obtained, and in combination with the results of sensitivity analysis, an approach for inverting natural gas hydrates using the attenuation characteristics of the dipole flexural wave is proposed. The results of the sensitivity analysis demonstrate that the attenuation of the dipole flexural wave is sensitive to gas hydrate saturation. Numerical results derived from synthetic logging data are provided to illustrate the viability of the inversion of gas hydrate saturation. Even when significant noise is introduced into the receiver signal arrays, the inversion method remains stable and accurately assesses gas hydrate saturation. The correctness and effectiveness of the proposed approach are substantiated through the processing of numerical simulation data. This work provides a potent processing approach for evaluating reservoir hydrate saturation utilizing acoustic well-logging information.

Identification of large yellow croakers (Larimichthys crocea) scavenger receptor genes: Involvement in immune response to Pseudomonas plecoglossicida infection and hypoxia-exposure experiments - Xuanyang Sun; Ning Bao; Chen Rui; Yadong Xue; Qian Fang; Tianyu Zheng; Ziyang Lin; Xiumei Liu; Xubo Wang (Fish & Shellfish Immunology, 2024)

Regulatory dynamics of the higher-plant PSI–LHCI supercomplex during state transitions - Jianghao Wu; Shuaijiabin Chen; Chao Wang; Weijun Lin; Chao Huang; Chengxu Fan; Dexian Han; Dandan Lu; Xiumei Xu; SenFang Sui; Lixin Zhang (Molecular Plant, 2023)

Aquaculture environment changes fish behavioral adaptability directly or indirectly through personality traits: a case study - Zonghang Zhang; Wuhan Lin; Dongjian He; Quanming Wu; Canrui Cai; Huaxuan Chen; Yangke Shang; Xiumei Zhang (Reviews in Fish Biology and Fisheries, 2023)

Physical enrichment for improving welfare in fish aquaculture and fitness of stocking fish: A review of fundamentals, mechanisms and applications - Zonghang Zhang; Wuhan Lin; Yunqi Li; Xianyu Yuan; Xianqing He; Hancheng Zhao; Jiezhang Mo; Jianqing Lin; Liangliang Yang; Bo Liang; Xiumei Zhang; Wenhua Liu (Aquaculture, 2023)

Genetic variants of SOS2, MAP2K1 and RASGRF2 in the RAS pathway genes predict survival of HBV-related hepatocellular carcinoma patients - Qiuling Lin; Moqin Qiu; Xueyan Wei; Zhouyun xiang; Zihan Zhou; Iiangyan Ji; Xiumei Liang; Xianguo Zhou; Qiuping Wen; Yingchun Liu; Hongping Yu (Archives of Toxicology, 2023)

Purinergic signaling: a potential therapeutic target for depression and chronic pain - Yuting Zou; Runan Yang; Lin Li; Xiumei Xu; Shangdong Liang (Purinergic Signalling, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

An Evaluation of the Coupling Coordination of Technological Innovation System in China’s Marine Biopharmaceutical Industry - Xiumei Fu; Yangming Zheng; Chunyu Lin; Ping Wang; Changyun Wang (Journal of Ocean University of China, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

Study of the Involvement of the P2Y12 Receptor in Chronic Itching in Type 2 Diabetes Mellitus - Xiumei Xu; Huiqing Zhang; Lin Li; Runan Yang; Guilin Li; Shuangmei Liu; Günther Schmalzing; Hong Nie; Shangdong Liang (Molecular Neurobiology, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Acoustic Wave Propagation in a Borehole with a Gas Hydrate-Bearing Sediment - Lin Liu; Xiumei Zhang; Yunjia Ji; Xiuming Wang (Journal of Marine Science and Engineering, 2022)
A knowledge of wave propagation in boreholes with gas hydrate-bearing sediments, a typical three-phase porous medium, is of great significance for better applications of acoustic logging information on the exploitation of gas hydrate. To study the wave propagation in such waveguides based on the Carcione–Leclaire three-phase theory, according to the equations of motion and constitutive relations, a staggered-grid finite-difference time-domain (FDTD) scheme and a real axis integration (RAI) algorithm in a two-dimensional (2D) cylindrical coordinate system are proposed. In the FDTD scheme, the partition method is used to solve the stiff problem, and the nonsplitting perfect matched layer (NPML) scheme is extended to solve the problem of the false reflection waves from the artificial boundaries of the computational region. In the RAI algorithm, combined with six boundary conditions, the displacement potentials of waves are studied to calculate the borehole acoustic wavefields. The effectiveness is verified by comparing the results of the two algorithms. On this basis, the acoustic logs within a gas hydrate-bearing sediment are investigated. In particular, the wave field in a borehole is analyzed and the amplitude of a Stoneley wave under different hydrate saturations is studied. The results indicate that the attenuation coefficient of the Stoneley wave increases with the increase of gas hydrate saturation. The acoustic responses in a borehole embedded in a horizontally stratified hydrate formation are also simulated by using the proposed FDTD scheme. The result shows that the amplitude of the Stoneley wave from the upper interface is smaller than that from the bottom interface.

Morphological characteristics and DNA barcoding of Pampus echinogaster (Basilewsky, 1855) - Yuan Li; Yan Zhang; Tianxiang Gao; Zhiqiang Han; Longshan Lin; Xiumei Zhang (Acta Oceanologica Sinica, 2017)

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Anti-inflammatory Effect of Acetylpuerarin on Eicosanoid Signaling Pathway in Primary Rat Astrocytes - Yanxiao Xiang; Xinbing Wei; Lin Chen; Huiqing Liu; Xiaoqian Liu; Tian Wang; Xiumei Zhang (Journal of Molecular Neuroscience, 2014)

Characterization of an avian influenza virus of subtype H4N6 isolated from ducks in the northern China - Chuantian Xu; Mei Lu; Beixia Hu; Shaohua Yang; Qinghua Huang; Lin Zhang; Xiumei Zhang (Virus Genes, 2014)

Biodegradation of poly(ε-caprolactone) (PCL) by a new Penicillium oxalicum strain DSYD05-1 - Fan Li; Dan Yu; Xiumei Lin; Dongbo Liu; Hongmei Xia; Shan Chen (World Journal of Microbiology and Biotechnology, 2012)